Strategi Pemasaran dan Kualitas Pelayanan terhadap Profitabilitas Usaha Koperasi Produksi Susu Peternakan - Sugandi, Alan (Jurnal Aplikasi Manajemen, 2013)
Low quality of institutions and organization of cooperatives led to lagging performance and the lack of good image of cooperatives in the community. Lack of understanding of the cooperative as a business entity that has the institutional structure (organizational structure, power structure, and incentive structures) is unique/distinctive compared to other business entities, as well as less socializing information about the practices of cooperatives the right (best practices) have led to various problems fundamental obstacles to the advancement of cooperatives in Indonesia. The purpose of this study was to: (1) analyze the relationship marketing strategy on the performance of KPS Enterprises Bogor, (2) analyze the relationship Quality Service to Business Performance KPS Bogor, (3) whether against relationship between Strategic Marketing and Quality Service to Business Performance KPS Bogor. The results showedthat: (1) marketing strategy has a very close relationship and have a very positive influence on business performance, it is seen from the results of Pearson correlation coefficient test for 87.9%, (2) The results of Pearson correlation analysis at 80,7% for the variable quality of service indicating that the relationships formed are very strong and has a very positive influence, and, (3) The results of testing the relationship together indicate that the marketing strategy and service quality has a very close relationship to business performance, this seen from the test results showed the R square of 72,2% and it can be concluded that the relationships formed are very good and have a positive influence on business performance of KPS Bogor.